Pola Komunikasi Orangtua Dalam Mengawasi Penggunaan Gawai Pada Generasi Alpha di Kabupaten Deli Serdang - Husnah, Raudha Hasanatul; Hardiyanto, Sigit (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
In today's digital era, the use of gadgets by children has become common and unavoidable. Technology offers various educational and entertainment benefits so that without adequate supervision from parents, children are at risk of being exposed to inappropriate content and experiencing negative impacts on child development. The purpose of this study was to find out how parents communicate with their children to provide understanding regarding things in gadget use. The method in this study is to use a qualitative descriptive method, with data collection techniques through observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, and drawing conclusions. Researchers conducted interviews with 5 parents in Deli Serdang Regency who have children in the alpha generation category. The results of the study showed that there were authoritarian communication patterns and democratic communication patterns used by parents in supervising gadget use in children